2016
DOI: 10.1111/bcp.13161
|View full text |Cite
|
Sign up to set email alerts
|

Sertraline use in the first trimester and risk of congenital anomalies: a systemic review and meta‐analysis of cohort studies

Abstract: This meta-analysis suggested that the use of sertraline use by pregnant women in the first trimester had an increased risk of cardiovascular-related malformations as well as atrial and/or ventricular septal defects in infants. Meanwhile, nonsignificant associations between sertraline use and other congenital anomalies were found. More cohort studies are warranted to provide detailed results of other congenital anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
31
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 61 publications
7
31
1
1
Order By: Relevance
“…Retrieved studies were excluded from our meta‐analysis if they met any of the following criteria : (1) letters, editorials, case reports, reviews, meta‐analyses, notes or studies conducted in animals; (2) used case–control, cross‐sectional or clinical trial designs; (3) defined the fluoxetine exposure period as the second and/or third trimester; (4) did not provide sufficient risk estimates (i.e., OR, risk ratio or relative risk) with 95% CI, or did not provide sufficient data to calculate risk estimates; or (5) were not published in English.…”
Section: Methodsmentioning
confidence: 99%
“…Retrieved studies were excluded from our meta‐analysis if they met any of the following criteria : (1) letters, editorials, case reports, reviews, meta‐analyses, notes or studies conducted in animals; (2) used case–control, cross‐sectional or clinical trial designs; (3) defined the fluoxetine exposure period as the second and/or third trimester; (4) did not provide sufficient risk estimates (i.e., OR, risk ratio or relative risk) with 95% CI, or did not provide sufficient data to calculate risk estimates; or (5) were not published in English.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to SSRIs, database studies that have not controlled for maternal depression have reported an increased risk of cardiac septal defects in neonates exposed to SSRIs in utero (Gao et al, 2018;Kallen and Otterblad, 2007;Shen et al, 2017), but for the majority of SSRIs this effect is no longer statistically significant when maternal depression (Gao et al, 2018;Huybrechts et al, 2014) and lifestyle risk factors are controlled for (Huybrechts et al, 2014); data relating to sertraline are insufficient to allow an effect to be excluded (Gao et al, 2018).…”
Section: Selective Serotonin Reuptake Inhibitor (Ssri) Antidepressantmentioning
confidence: 99%
“…Subsequent studies have implicated other antidepressants, including all commonly used SSRIs and clomipramine (Reis and Kallen, 2010;Shen et al, 2016).…”
Section: Teratogenicitymentioning
confidence: 99%